Foundations of sustainable business : theory, function, and strategy - Sanders, Nada R.; Wood, John D. (Hoboken, NJ : John Wiley & Sons, Inc., 2024)
"We designed this book to show how and why business every aspect of business must focus on sustainability -first introducing business topics as they are traditionally presented in a business or MBA program, then explaining how each topic has changed in light of the sustainability imperative. By integrating cases of social and environmental leadership in the private sector, we present the various managerial-class disciplines in a new light. We eschew the traditional economic single-mindedness of managerial decision-making and instead foster an appreciation for the social and environmental ramifications of business decisions, both to avoid risk (defensive strategy) and to find new ways to create value (proactive strategy)"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Management -- Environmental aspects; Industries -- Environmental aspects; Business enterprises -- Environmental aspects; Sustainable development